Can integrated social protection programmes affect social cohesion? Mixed-methods evidence from Malawi - Francesco Burchi; Federico Roscioli (Deutsches Institut für Entwicklungspolitik (DIE), 2021)
The primary objective of social protection is to fight poverty and food insecurity. However, there are good theoretical arguments to support the idea that it can also contribute to more complex outcomes, such as social cohesion. This paper investigates the effects of the Tingathe Economic Empowerment Programme (TEEP) in Malawi on three key pillars of social cohesion, namely inclusive identity, trust and cooperation. The TEEP is a multi-component social protection scheme, which targets ultra-poor and labor-constrained households. It provides three randomly selected groups of beneficiaries with three different packages: a lump-sum transfer, a financial and business training connected to the creation of saving (VSL) groups, and a combination of both. A sequential mixed-methods approach was employed to assess the effects of the different project components. This consists of: i) a quantitative analysis based on an experimental design and primary data collected one year after project implementation; ii) a qualitative analysis, based on focus group discussions and individual interviews conducted three years after project implementation. [...]
Keywords: 330